2004
DOI: 10.1016/s0896-6273(04)00047-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging of Macaque Monkeys Performing Visually Guided Saccade Tasks

Abstract: The frontal and parietal eye fields serve as functional landmarks of the primate brain, although their correspondences between humans and macaque monkeys remain unclear. We conducted fMRI at 4.7 T in monkeys performing visually-guided saccade tasks and compared brain activations with those in humans using identical paradigms. Among multiple parietal activations, the dorsal lateral intraparietal area in monkeys and an area in the posterior superior parietal lobule in humans exhibited the highest selectivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
206
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(240 citation statements)
references
References 71 publications
32
206
2
Order By: Relevance
“…This finding is consistent with most electrophysiological studies of LIP and with the strong contralateral bias reported in an fMRI study (3,7,27,28; but see ref. 8).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with most electrophysiological studies of LIP and with the strong contralateral bias reported in an fMRI study (3,7,27,28; but see ref. 8).…”
Section: Discussionsupporting
confidence: 91%
“…A newly discovered map was found in the inferior frontal sulcus, just anterior to the precentral sulcus (highlighted with a white bounding box). Another map was found in superior precentral sulcus (sup-PCS); this location corresponds to the FEF, an area involved in eye movements and visual attention (Paus, 1996;Corbetta et al, 1998;Beauchamp et al, 2001;Koyama et al, 2004). Note that the more anterior and inferior prefrontal foci active during the 2-back face identity task do not appear to contain spatial maps.…”
Section: Resultsmentioning
confidence: 97%
“…Of particular interest is a neuroimaging experiment [20] that used the same saccade paradigm both in humans and macaque monkeys, namely the species in which area LIP has been defined physiologically. The results suggested a functional correspondence between the dorsal subdivision of area LIP in the monkey with the posterior IPS region in the human brain [20].…”
Section: Discussionmentioning
confidence: 99%